Pengaruh penundaan pemeriksaan terhadap laju endap darah pada sampel darah EDTA - Jeremia, Ivan Benny Lino (Journal of Evidence-based Nursing and Public Health, 2024)
Introduction: Blood is an essential component of living organisms, ranging from primitive animals to humans. Under physiological conditions, blood always remains within blood vessels to carry out its functions (Bakta, 2020). The Erythrocyte Sedimentation Rate (ESR), also known as blood sedimentation rate, is an examination to determine the rate at which erythrocytes settle in non-coagulated blood (blood containing anticoagulants) in a vertical tube over a specific period. The Westergren method for ESR measurement is the most satisfactory method currently used in hospitals and clinics. This study aims to determine the difference in Erythrocyte Sedimentation Rate values between EDTA blood samples examined immediately and those delayed for 3 hours at room temperature. Method: This analytical descriptive research compares the results of Erythrocyte Sedimentation Rate examinations conducted immediately and those delayed for 3 hours using the Westergren method at room temperature. The study involved 30 samples obtained from outpatient and inpatient patients by venous blood collection. Findings: The statistical analysis using Paired t-Test showed that the P Value was 0.00 (P < 0.05), indicating a significant difference between immediate and delayed examinations for 3 hours at room temperature using the Westergren method. Conclusion: Based on the research findings, it is recommended to conduct Erythrocyte Sedimentation Rate examinations with EDTA blood samples immediately as it is more effective.